The effects of 2-methoxyethanol and 2-ethoxyethanol on hematological changes induced by 2-butoxyethanol - Beata Starek-Świechowicz; Katarzyna Miranowicz-Dzierżawska; Bogusława Budziszewska; Andrzej Starek (Nofer Institute of Occupational Medicine, 2015)
Background: Alkoxyethanols (ethylene glycol alkyl ethers) are used as mixtures in a variety of industrial and household products. The aim of this study has been to evaluate the effects of 2-methoxyethanol (ME) and 2-ethoxyethanol (EE) on hematological changes induced by 2-butoxyethanol (BE) in rats. Material and Methods: Experiments were performed on male Wistar rats treated subcutaneously with BE, ME, and EE alone (in the dose of 0.75 mM/kg/day and 1.25 mM/kg/day) and their mixtures with the molar ratio 1:1, for 4 weeks. Hematological analyses were performed on the day 0, 4, 11, 18, and 29. Hemoglobin (HGB) concentration in the urine was also determined in the rats treated with BE alone and co-exposed to BE and ME and also BE and EE. Results: The rats co-exposed to BE and ME or BE and EE demonstrated significantly less pronounced hematological changes in comparison with animals treated with BE alone at the beginning of exposure. At the later period the hematological alterations in the same animals were markedly pronounced and progressing with exposure time. The rats co-exposed to BE and ME or BE and EE did not demonstrate hemoglobinuria. Conclusions: ME or EE co-administered to rats with BE lead to the amelioration in the majority of the hematological parameters at the beginning of the exposure. The hematological changes at the end of the co-exposure to BE and ME or BE and EE were markedly pronounced. The effects observed in this study appear to be related with metabolic interactions of the examined ether. Med Pr 2015;66(3):303-315